Current approaches in management of patients with keratoconus - Gănescu, Alexandra Mădălina (Medicine and Pharmacy Reports, 2022)
Keratoconus is a relatively frequent eye disease, especially in young patients, in which the cornea gradually thins and deforms in a cone shape. In the past, it could be treated only with glasses, rigid contact lenses or, for advanced cases, penetrating corneal transplant. Nowadays, corneal cross-linking, intracorneal ring segments implantation or deep anterior lamellar keratoplasty are available options of treatment, along with the above mentioned ones. Several studies focused on this disease and its management attempted to establish the applicability of these treatment methods in current practice. In the early stages, glasses or soft toric contact lenses are able to correct the astigmatism, but, as the disease progresses, rigid contact lenses are indicated. Corneal cross-linking is done in order to slow down or even stop the progression of the disease. Implanting intracorneal ring segments helps improve visual acuity in patients with low vision that cannot be corrected otherwise. Advanced stages need corneal transplant, either penetrating or anterior lamellar, depending on each patient’s ocular characteristics. Thus, keratoconus treatment is individualized for every patient, according to the stage of the disease. Moreover, because of the new developed technology, keratoconus patients can benefit from efficient treatment, in much safer conditions.